Sportliche Belastungsfähigkeit bei orthopädischen Deformitäten der Wirbelsäule im Kindesalter - Schmitt, H.; Carstens, C. (Deutsche Zeitschrift für Sportmedizin, 2002)
Spinal deformities can reduce physical resilience. Recommendations are made with regard to the degree of deformity and the expected growth. Children with scoliosis more than 20° (Cobb) should take part in sports, because no studies exist which show that special disciplines increase the deformity of the spine. Recommendations after spinal surgery are made individually with regard to the length of fusions. Physical activity seems to influence the degree of kyphosis. Children with M. Scheuermann and acute backache shouldn`t take part in sports, in adulthood recommendations are made with regard to the degree of deformity and the resilience of the anterior parts of the spine. Children with spondylolysis and acute backache are not able to do sports, clinical and radiological checks are required. Children with spondylolysis or spondylolisthesis shouldn`t take part in sports with hyperextensive or rotatory loads. There exist only a few scientific examinations about sports and spinal deformities, recommendations essentially base on empirical data.